Smart Mesoporous Silica Nanoparticles for Protein Delivery - Liu, Hai-Jun (Nanomaterials (Basel), 2019)
Mesoporous silica nanoparticles (MSN) have attracted a lot of attention during the past decade which is attributable to their versatile and high loading capacity, easy surface functionalization, excellent biocompatibility, and great physicochemical and thermal stability. In this review, we discuss the factors affecting the loading of protein into MSN and general strategies for targeted delivery and controlled release of proteins with MSN. Additionally, we also give an outlook for the remaining challenges in the clinical translation of protein-loaded MSNs.